A study to assess the impact of medical nutrition therapy compared to standard nutrition therapy in children with severe thinness in the age group of 5 to 10 years - Vishal D Sawant; Prachi Karnik; Varun Viswanathan; Blossom Rodrigues; Lavina Fernandes; Alka Jadhav (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of our study was to study and compare the impact and efficacy of medical nutrition therapy (MNT) with that of the standard nutrition therapy(SNT) in children diagnosed with Severe thiness in the age group of 5-10 years and diagnosed as severely thin. Study Design: It was a prospective comparative study, conducted over a period of 18 months at the Nutrition Rehabilitation, Research and Training Centre (NRRTC) associated with a tertiary care hospital in India. Methods and Materials: A total of 113 children in the age group of 5 to 10 years with severe thinness were enrolled and divided into 2 groups-58 were placed in the MNT group and 55 in the SNT group for a period of 8 weeks. The children in both groups received MNT and SNT diet over the said period of 8 weeks. Primary outcome variables were weight gain and body mass index (BMI) (i.e., change in nutritional status). Results: At the end of 8 weeks, the rate of weight gain (gm/kg/day) was significantly greater in the MNT group, that is, 2.35 gm/kg/day as compared with the SNT group, that is, 0.73 gm/kg/day, and the change in nutritional status was significantly better in the MNT group (p < 0.001) with 62.1% achieving normal nutritional status, 32.8% remaining thin, and 5.2% remaining severely thin as compared to the SNT group in which 9.1% achieved normal nutritional status, 65.5% remained thin, and 25.5% remained severely thin. Conclusion: To conclude, MNT is superior to SNT for the treatment of severe thinness (ST).